Disease stratification in giant cell arteritis to reduce relapses and prevent long-term vascular damage. (December 2021) - Tomelleri, Alessandro; van der Geest, Kornelis S M; Sebastian, Alwin; van Sleen, Yannick; Schmidt, Wolfgang A; Dejaco, Christian; Dasgupta, Bhaskar
Summary: For years, clinicians and researchers working on giant cell arteritis have been battling with the conundrum of a disease that displays a short-term steroid responsiveness but is burdened by a remarkable risk of flares and chronic damage in the long term. This issue should be addressed by a change in the direction of research and clinical practice. Evidence suggests that giant cell arteritis is not a monolithic disease; it varies in extent and severity. Hence, treatment should be guided by disease stratification. The current one-size-fits-all strategy leads to overreliance on glucocorticoids and progression of glucocorticoid-related and disease-related complications. A new approach requires disease stratification using clinical, laboratory, histology, and imaging parameters. A giant cell arteritis registry might offer opportunities to scrutinise disease course and prognostic variables early; however, more studies that directly incorporate disease stratification through the above parameters are required. This Series paper also suggests that future clinical trials should be targeted at patients with different disease strata of giant cell arteritis and should incorporate ultrasound, PET-CT scanning, and other imaging modalities as key outcomes.